2006
DOI: 10.1016/j.neulet.2006.09.066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucose concentration on redox status in rat primary cortical neurons under hypoxia

Abstract: Reduced supply of glucose involves in many pathological conditions such as stroke and contributes to ischemic injuries. In contrast, hyperglycemia has also been regarded as an important factor in causing and exaggerating stroke damage. Although the molecular mechanism(s) of imbalanced glucose-induced cellular injuries under low oxygen conditions are not clear, oxidative stress has been implicated in both hypo-and hypeglycemic damage. Redox status is critical for the regulation of cellular signaling and cell su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 30 publications
6
30
0
1
Order By: Relevance
“…Intracellular ROS and hydroxyl radical accumulation induced lipid peroxidation (LPO) (30); thus, lipid molecules were consumed uninterruptedly, decreasing the amount of unsaturated fatty acid and affecting the fluidity of biological membranes (31). MG and other aldehydes react with proteins and enzymes, which cause them to lose their biological activity and lead to an abnormal metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular ROS and hydroxyl radical accumulation induced lipid peroxidation (LPO) (30); thus, lipid molecules were consumed uninterruptedly, decreasing the amount of unsaturated fatty acid and affecting the fluidity of biological membranes (31). MG and other aldehydes react with proteins and enzymes, which cause them to lose their biological activity and lead to an abnormal metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both glucose deprivation and high glucose exposure have been shown to be toxic to cells. Incubating with elevated glucose levels can also induce neuronal death in PC12 cells (Shi and Liu 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that glucose deprivation causes perturbations in cellular sensitivity to oxidative stress, which is mediated by increased generation of pro-oxidants and decreased scavenging of free radicals. In primary dorsal root ganglion neurons, glucose (45 mM) rapidly induces a rise in ROS, and the toxicity induced by high glucose is blocked by inhibiting ROS induction (Shi and Liu 2006). However, no detailed study has been carried out to evaluate the inhibitory effect of saffron on high glucose-induced neurotoxicity in PC12 cells as an in vitro model for diabetic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Diversos estudos in vivo e in vitro demonstraram que a hiperglicemia a curto prazo protege miĂłcitos cardĂ­acos e neurĂ´nios [45][46][47] . .…”
Section: S132unclassified